A Heterozygous CFHR3-CFHR1 Gene Deletion in a Pediatric Patient With Transplant-associated Thrombotic Microangiopathy Who was Treated With Eculizumab. Issue 8 (November 2018) - Nozawa, Akifumi; Ozeki, Michio; Hori, Tomohiro; Kawamoto, Norio; Hirayama, Masahiro; Azuma, Eiichi; Fukao, Toshiyuki
Abstract : Complement system dysregulation, such as complement Factor H (CFH) autoantibodies and deletions in CFH-related ( CFHR ) genes 3 and 1, might cause transplant-associated thrombotic microangiopathy (TA-TMA). The use of eculizumab, a terminal complement inhibitor, could be a targeted therapy for TA-TMA. We report a 1-year-old girl who developed TA-TMA, just after autologous peripheral blood stem cell transplantation in neuroblastoma therapy. Eculizumab improved TA-TMA. Investigation for the complement alternative pathway showed a heterozygous CFHR3 - CFHR1 gene deletion, which is involved in complement activation. The patient might develop TA-TMA as a result of complement regulatory gene mutation.